Spatial confinement, self-polarization and exciton–phohon interaction effect on the location of exciton line in lead iodide nanofilms - Kramar, V.M.; Pugantseva, O.V.; Derevyanchuk, A.V. (Физика низких температур, 2014)
Theoretical investigation of the spatial confinement, self-polarization and exciton–phonon interaction influence on the exciton state in plane double nanoheterostructure (nanofilm)–lead iodide in polymeric matrix is performed within the effective mass approximation for the electron and dielectric continuum for the phonons in the framework of infinitely deep single quantum well. It is shown that spatial confinement is the dominating feature determining the energy of the bottom of exciton ground band and its binding energy. The relationship of two others depends on nanofilm thickness: in ultrathin films the influence of self-polarization effect is essentially bigger than the role of exciton–phonon interaction.